Impact of Frailty on Health Care Resource Utilization and Costs of Care in Myelodysplastic Syndromes. Issue 4 (10th April 2023) - Mozessohn, Lee; Li, Qing; Liu, Ning; Leber, Brian; Khalaf, Dina; Sabloff, Mitchell; Christou, Grace; Yee, Karen; Chodirker, Lisa; Parmentier, Anne; Siddiqui, Mohammed; Mamedov, Alexandre; et al.
Abstract : PURPOSE: The role of frailty in affecting survival in myelodysplastic syndromes (MDS) is increasingly recognized. Despite this, a paucity of data exists on the association between frailty and other clinically meaningful outcomes including health care resource utilization and costs of care. METHODS: We linked the Ontario subset of the prospective Canadian MDS registry (including baseline patient/disease characteristics) to population-based health system administrative databases. Baseline frailty was calculated from the 15-item MDS-specific frailty scale (FS-15). Primary outcomes were public health care utilization and 30-day standardized costs of care (2019 Canadian dollars) determined for each phase of disease (initial, continuation, and terminal phases). Negative binomial regression was used to assess the association between frailty and health care costs with Poisson regression to explore predictors of hospitalization. RESULTS: Among 461 patients with complete FS-15 scores, 374 (81.1%) had a hospitalization with a mean length of stay of 10.6 days. Controlling for age, comorbidities, Revised International Prognostic Scoring System, and transfusion dependence, the FS-15 was independently associated with hospitalization during the initial ( P = .02) and continuation ( P = .01) phases but not the terminal disease phase ( P = .09). The mean 30-day standardized cost per patient was $8, 499 (median, $6, 295; interquartile range, $2, 798-$11, 996), largely driven by cancer clinic visits and hospitalization. On multivariable analysis, the FS-15 was independently associated with costs of care during the initial disease phase ( P = .02). CONCLUSION: We demonstrate an association between frailty and clinically meaningful outcomes including hospitalization and costs of care in patients with MDS. Our results suggest that baseline frailty may help to inform patients and physicians of expected outcomes.